High-sensitive troponin T: a novel biomarker for prognosis and disease severity in patients with pulmonary arterial hypertension - Filusch, Arthur; Giannitsis, Evangelos; Katus, Hugo; Meyer, Franz Joachim (Clinical science, 2010)
PAH (pulmonary arterial hypertension) is the leading cause of fatal right ventricular failure. However, rarely detectable, cTnT [cardiac TnT (troponin T)] is a significant prognostic marker. Therefore the aim of the present study was to evaluate the usefulness of a novel high-sensitive cTnT (hsTnT) assay as a parameter for functional and prognostic evaluation of PAH patients. In 55 PAH patients (idiopathic, n=20; chronic thromboembolic, n=30; and interstitial lung disease, n=5) with a mean pulmonary artery pressure of 45±18 mmHg, cTnT was measured by a fourth-generation conventional assay and a novel hsTnT assay with a lower detection limit at 2 pg/ml [total imprecision <10% at the 99th percentile value (13.4 pg/ml)]. In 90.9% of patients, cTnT was detectable using the hsTnT assay and in 30.9% using the fourth-generation assay. Concentrations >99th percentile were observed in 27.3% using hsTnT compared with 10.9% using the fourth-generation assay. A total of five out of six patients with cTnT values >30 pg/ml (fourth-generation assay) or >29.5 pg/ml (hsTnT assay) died during the 12-month follow-up. There was a correlation between hsTnT and 6-min walk distance (r=−0.92, P=0.0014), right ventricular systolic strain (r=0.95, P=0.0018) and strain rate (r=0.82, P=0.0021). In AUC (area under the curve) analysis, hsTnT predicted death at least as effectively as hFABP (heart-type fatty-acid-binding protein) or NT-proBNP (N-terminal pro-brain natriuretic protein). Moreover, hsTnT predicted a WHO (World Health Organization) functional class >II better than NT-proBNP or hFABP. In conclusion, in PAH patients, the novel biomarker hsTnT is associated with death and advanced WHO functional class, and is related to systolic right ventricular dysfunction and an impaired 6-min walk distance.
Gesehen am 24.04.2023